Diversity of sambal types in Indonesia - L. L. Rahmah; A. N. M. Ansori (Пищевые системы, 2023)
Sambal is a processed chili paste with a spicy taste. The history of sambal begins with the arrival of chili seeds brought by the Portuguese in the 16th century, which was like a cultural renaissance of spicy foods. The methodology used for this research included analysis of food ethnographic literature, origin, function and types of sambal found in relevant articles and book chapters. The results show that the population with the highest consumption of sambal lives on the Sumatra Islands. There are two types of sambal preparation methods, namely slicing and mashing. Some chili sauces can be cooked or eaten raw. Sambal diversity is influenced by several factors, namely resources, geographical factors, history, and culture. Thus, sambal is considered to be an important contributor to food diversity in Indonesia because every local cuisine includes sambal and it is never left behind.